Cross-cultural management an introduction - Thomas, David C. (David Clinton) 1947-; Inkson, Kerr (SAGE Publications, Inc., 2022)
"We are reminded daily of the globally interconnected business world in which we live. Events on one side of the globe reverberate instantaneously in the other. Globalization has many effects, but one of the most important is the dramatic increase in the opportunity and need to interact with people who are culturally different from us. We are exposed on a daily basis to a wide variety of attitudes, values, beliefs, and assumptions that culturally different individuals hold about appropriate behavior. In order to thrive, and in some cases even to survive, as managers, we must learn to understand and integrate these differences. David Thomas and Kerr Inkson, offer students an authoritative, yet approachable perspective in Introduction to Cross-Cultural Management, 1st Edition"--Provided by publisher.